2020
DOI: 10.1021/acs.est.0c05651
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Surface Contamination, Stability, and Disinfection Data on SARS-CoV-2 (Through July 10, 2020)

Abstract: We conducted a systematic review of hygiene intervention effectiveness against SARS-CoV-2, including developing inclusion criteria, conducting the search, selecting articles for inclusion, and summarizing included articles. Overall, 96 268 articles were screened and 78 articles met inclusion criteria with outcomes in surface contamination, stability, and disinfection. Surface contamination was assessed on 3343 surfaces using presence/absence methods. Laboratories had the highest percent positive surfaces (21%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 106 publications
0
60
0
1
Order By: Relevance
“…After completing title, abstract, and full-text review of 104,735 articles, 109 articles meeting inclusion criteria were identified, with 33 additional articles identified from reference chaining. Information on surface disinfection has been published separately 8 ; herein we described results from 58 mask disinfection and reuse summaries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After completing title, abstract, and full-text review of 104,735 articles, 109 articles meeting inclusion criteria were identified, with 33 additional articles identified from reference chaining. Information on surface disinfection has been published separately 8 ; herein we described results from 58 mask disinfection and reuse summaries.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a previously described systematic review to identify and summarize WASH intervention effectiveness at interrupting SARS-CoV-2 transmission routes. 8 The review was developed based on the guidelines for the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 9 and for mask disinfection and reuse included: 1) a search strategy; 2) inclusion criteria; 3) a selection and data extraction strategy; 4) a framework for appraising risk of bias; and, 5) an analysis plan. Each of these steps is briefly described below (for more information see 8 ).…”
Section: Methodsmentioning
confidence: 99%
“… 6 , 8 , 9 A recent meta-analysis summarized the published results of SARS-CoV-2 RNA contamination on surfaces in different environments, revealing that 21% of the testing surfaces in testing laboratories and 17% of the testing surfaces in COVID-19 patient rooms were positive in PCR tests. 10 The viable virus can be isolated for up to 28 days on common surfaces (glass, stainless steel, etc.) by postinoculation 11 and was also found on the surface of the cold-chain food package.…”
Section: Introductionmentioning
confidence: 99%
“…In COVID-19 ICUs, the risk of environmental contamination is exacerbated by commonly used aerosolizing practices and procedures, including endotracheal intubation, cardiopulmonary resuscitation, ventilation, and tracheotomies [11][12][13][14]. In addition, SARS-CoV-2 viral particles can persist on surfaces for up to 9 days with fomite-dependent halflives ranging from 2.3-17.9 h on stainless steel, plastic, and nitriles-all surfaces commonly found in hospitals [15,16]. The potentially high infectivity of COVID-19 has generated uncertainty regarding how to manage patients diagnosed with COVID-19 while preventing in-hospital and intra-departmental dissemination of SARS-CoV-2 viral particles.…”
Section: Introductionmentioning
confidence: 99%